2012
DOI: 10.1017/jfm.2012.439
|View full text |Cite
|
Sign up to set email alerts
|

Double diffusive effects on pressure-driven miscible displacement flows in a channel

Abstract: The pressure-driven miscible displacement of a less viscous fluid by a more viscous one in a horizontal channel is studied. This is a classically stable system if the more viscous solution is the displacing one. However, we show by numerical simulations based on the finite-volume approach that, in this system, double diffusive effects can be destabilizing. Such effects can appear if the fluid consists of a solvent containing two solutes both influencing the viscosity of the solution and diffusing at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…It is found (not shown) that although at t = 0 the less (high) viscous fluid occupies the annular (core) region of the pipe, the double-diffusive phenomenon alters the viscosity variation at the later times by creating a highly viscous region near the wall, which is the main cause of instability observed in this case. A similar mechanism was previously observed by Mishra et al (2012) and Bhagat et al (2016) in the numerical simulations of displacement flows in planar channel and axisymmetric pipe in the presence of DD effect. On the other hand the dynamics for δ = 1 is dominated only by diffusive mixing.…”
Section: Direct Numerical Simulationssupporting
confidence: 83%
See 1 more Smart Citation
“…It is found (not shown) that although at t = 0 the less (high) viscous fluid occupies the annular (core) region of the pipe, the double-diffusive phenomenon alters the viscosity variation at the later times by creating a highly viscous region near the wall, which is the main cause of instability observed in this case. A similar mechanism was previously observed by Mishra et al (2012) and Bhagat et al (2016) in the numerical simulations of displacement flows in planar channel and axisymmetric pipe in the presence of DD effect. On the other hand the dynamics for δ = 1 is dominated only by diffusive mixing.…”
Section: Direct Numerical Simulationssupporting
confidence: 83%
“…The instabilities due to the influence of DD effect were also observed in other flow systems, e.g. displacement of a highly viscous fluid by a less viscous one in porous media (Mishra et al 2010;Swernath & Pushpavanam 2007), Hele-Shaw cell (Pritchard 2009), and in pressure-driven flow in a channel (Mishra et al 2012). A review of instabilities associated with DD effect in various flow configurations can be found in Govindarajan & Sahu (2014).…”
Section: Introductionmentioning
confidence: 83%
“…Sahu et al 37 showed that the above system becomes absolutely unstable for a certain range of parameters and have indicated the region of absolute and convective instabilities in the Reynolds number and viscosity ratio space. There are also several investigations 29,30,[38][39][40][41][42][43][44][45][46][47][48] not relevant to the present study (but worth mentioning in the present context) that deals with stability characteristics of viscosity stratified flows in rigid channels/pipes, involving the displacement of one fluid by another. The interesting features and the type of instabilities displayed by these flow systems with boundaries as either rigid walls or rigid circular pipes suggest that it is worth analyzing the analogous flow systems in configurations with velocity slip at the boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Again the values of concentration are set to one and zero above and below this line respectively. The reader is referred to Mishra et al (2012) for details of the numerical method used. The dotted lines with filled triangles in panel (a) and (b) represent the profiles obtained from these direct numerical simulations for R s = −1 Sc = 100, Re = 100 and t = 80.…”
Section: Formulationmentioning
confidence: 99%